Analysis of performance measures of Kanban production system - Arulanantham, George C.; Fujiwara, Okitsugu; Sharif, M. Nawaz; Vilas Wuwongse; The Government of Finland (Bangkok : Asian Institute of Technology, 1992)
In this paper, we analyze the performance measures (inventory and backorder) of the Kanban discipline for a production line, consisting of serial production stages. There is a fixed number of Kanban in each stages. A part produced at a stage must acquire one of these Kanbans to enter the succeeding stage and must continue to hold it throughout it sojourn there. Any unattached Kanbans that are present in the stage are to be found on the bulletin board and are considered as the request for the parts produced at preceding stage. Thus intermediate-product inventory is divided into two parts, inventory at the output buffer and inventory at the succeeding stage's input queue. There is a finite pool for raw part preceding the first stage and finite buffer for the demand following the final stage. We decompose each stage as a semi-autonomous component and construct a stochastic model for each isolated stage. We explained the number of parts in the output buffer and number of Kanbans in the bulletin board and number of parts in the input queue as a Markov process and provided the scheme to analyze the performance measures of the system. In addition to this, we introduced a stage with signal Kanban (produce the product as a lot) and provide the method to analyze the system.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1992
Keywords: Production management -- Mathematical models